The metal ion-dependent adhesion site motif of the Enterococcus faecalis EbpA pilin mediates pilus function in catheter-associated urinary tract infection - Nielsen, Hailyn V. (2014)
Though the bacterial opportunist Enterococcus faecalis causes a myriad of hospital-acquired infections (HAIs), including catheter-associated urinary tract infections (CAUTIs), little is known about the virulence mechanisms that it employs. However, the endocarditis- and biofilm-associated pilus (Ebp), a member of the sortase-assembled pilus family, was shown to play a role in a mouse model of E. faecalis ascending UTI. The Ebp pilus comprises the major EbpC shaft subunit and the EbpA and EbpB minor subunits. We investigated the biogenesis and function of Ebp pili in an experimental model of CAUTI using a panel of chromosomal pilin deletion mutants. A nonpiliated pilus knockout mutant (EbpABC− strain) was severely attenuated compared to its isogenic parent OG1RF in experimental CAUTI. In contrast, a nonpiliated ebpC deletion mutant (EbpC− strain) behaved similarly to OG1RF in vivo because it expressed EbpA and EbpB. Deletion of the minor pilin gene ebpA or ebpB perturbed pilus biogenesis and led to defects in experimental CAUTI. We discovered that the function of Ebp pili in vivo depended on a predicted metal ion-dependent adhesion site (MIDAS) motif in EbpA’s von Willebrand factor A domain, a common protein domain among the tip subunits of sortase-assembled pili. Thus, this study identified the Ebp pilus as a virulence factor in E. faecalis CAUTI and also defined the molecular basis of this function, critical knowledge for the rational development of targeted therapeutics. IMPORTANCE: Catheter-associated urinary tract infections (CAUTIs), one of the most common hospital-acquired infections (HAIs), present considerable treatment challenges for physicians. Inherently resistant to several classes of antibiotics and with a propensity to acquire vancomycin resistance, enterococci are particularly worrisome etiologic agents of CAUTI. A detailed understanding of the molecular basis of Enterococcus faecalis pathogenesis in CAUTI is necessary for the development of preventative and therapeutic strategies. Our results elucidated the importance of the E. faecalis Ebp pilus and its subunits for enterococcal virulence in a mouse model of CAUTI. We further showed that the metal ion-dependent adhesion site (MIDAS) motif in EbpA is necessary for Ebp function in vivo. As this motif occurs in other sortase-assembled pili, our results have implications for the molecular basis of virulence not only in E. faecalis CAUTI but also in additional infections caused by enterococci and other Gram-positive pathogens.